Effect of different feeding regimes on productive performances of HF × Kankrej crossbred cows - ISLAM, M M; SHAH, S V; PATEL, Y G; RAJPURA, R M (The Indian Journal of Animal Sciences, 2021)
Present experiment was conducted to study the effect of different feeding regimes on productive performances of HF × Kankrej crossbred cows. The study was conducted on 18 crossbred cows which were distributed into three treatment groups comprising of 6 animals each. Animals of T1 (Farmersâ€™ feeding) group were maintained as per the feeding regime followed by small and marginal farmers in India. Animals of T2 (Modified feeding) group comprised of feeding with scientific interventions. Animals of T3 (Farm feeding) group were fed as per feeding practices followed at Livestock Research Station, Anand Agricultural University. Milk yield and 4% Fat Corrected Milk (FCM) yield was significantly higher in T2 and T3 as compared to T1 group. Lactation yield was highest in T3 followed by T2 and T1 groups. Average total solid of milk was significantly more in T3 as compared to T1 and T2 groups. Milk fat was maximum in T3 followed by T2 and T1 groups which did not differ significantly among each other. SNF, protein and lactose content of milk was found significantly higher in T3 as compared to T1 and T2 groups. Milk salt was highest in T3 followed by T2 and T1 group which differed significantly among each other. It may be concluded from the present study that feeding regime significantly influenced productive performances of crossbred cows as modified feeding group performed better over farmers feeding group and at par with farm feeding group.